Melt pool controlled laser powder bed fusion for customised low-density lattice structures. (5th November 2019) - Großmann, Alexander; Felger, Julian; Frölich, Tilman; Gosmann, Julian; Mittelstedt, Christian
Abstract: Laser powder bed fusion is a promising technology enabling the manufacturing of complex parts such as cellular structures with superior mechanical properties. However, their fabrication is not straightforward, since the geometry of the melt track and the constitution of the melt pool significantly affects the dimensions of the final part. Thus, a sound understanding of the interrelation between process parameters, the melting process and the geometry of the melt track is of crucial importance in order to ensure high quality of the lattice. In this work, a scaling law is proposed that relates the width of a single melt track to process and material parameters. This is done employing dimensional analysis as well as an averaged energy balance. The predictive power of the proposed model is demonstrated based on extensive experimental data provided by the authors. Considering truss lattices, the present approach bridges the gap between manufacturing parameters and macroscopic characteristics of lattice structures. This ultimately enables a proactive adjustment of process parameters in order to tailor the lattice's geometry and the elastic properties. Moreover, the proposed modelling approach serves as a basis for an extended theory accounting for additional physical effects present in selective laser melting. Graphical abstract: Unlabelled Image